Upaya Meningkatkan Kualitas Tidur Anak-Anak Sekolah Dasar Dalam Era Game Online - Alya Naina Putri; Siti Rokmanah; A. Syachruroji (Journal on Education, 2023)
The popularity and technological development of online gaming has significantly affected the sleep quality of elementary school children. Many elementary school children play online games, however, they do not realize the consequences of playing online games excessively will have a negative impact, one of which is disruptep sleep quality. Parents need to play an active role in supervising and controlling their children’s online gaming activities so that they get adequate and quality sleep.